Physiatric Management of Carpal Tunnel Syndrome - Hasan, Md Israt; Emran, Mohammed; Newaz, Fatema; Md Atiquzzaman, -; Morshed, Tawfiq; Banik, Amitav; Sadeque, ABM Zafar; Sharmin, Shaila (KYAMC Journal, 2020)
Carpal Tunnel Syndrome (CTS) is the most common entrapment neuropathy of the upper limb. Diagnosis of CTS was rare before middle of the nineteenth century but in recent years it continues to be made with increasing frequency by the virtue of wide spread public awareness and highly specific diagnostic tests. Individuals engaged in repetitive works which involves flexion and extension of the wrist, strong grip or exposure to vibration are particularly at risk of developing the disease. It is now accounted amongst the common work related claimed disabilities in our country. KYAMC Journal Vol. 10, No.-4, January 2020, Page 206-210